In Zehn Tagen Bin Ich Tot - Galfetti, Aurelio (Switzerland, 2013)
This film follows the life of prisoners on Death Row, waiting for a final sentence to be given. Raoul has just been given the date of his execution.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Fiction films